2007
DOI: 10.1111/j.1467-789x.2007.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ‘fun foods’: nutritional content and analysis of supermarket foods targeted at children

Abstract: This article provides a nutritional profile of foods targeted specifically at children in the Canadian supermarket. Excluding confectionery, soft drinks and bakery items, 367 products were assessed for their nutritional composition. The article examines the relationship between 'fun food' images/messages, product claims and actual product nutrition. Among other findings, it concludes that approximately 89% of the products analysed could be classified as of poor nutritional quality owing to high levels of sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
114
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 9 publications
16
114
0
13
Order By: Relevance
“…At the outset, it is important to note that the codes for child marketing and nutrition were developed as cumulative measures of both types of marketing approaches, as the presence of more of these cues indicates a more concerted effort to highlight these particular attributes. Development for the childtargeted marketing code was based on previous research (20,(30)(31)(32)(33) . Each package was assessed for the presence of each of the following eight characteristics: (i) child-friendly imagery (e.g.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…At the outset, it is important to note that the codes for child marketing and nutrition were developed as cumulative measures of both types of marketing approaches, as the presence of more of these cues indicates a more concerted effort to highlight these particular attributes. Development for the childtargeted marketing code was based on previous research (20,(30)(31)(32)(33) . Each package was assessed for the presence of each of the following eight characteristics: (i) child-friendly imagery (e.g.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…Nevertheless, there are few studies that have analysed the Na content of processed foods consumed by children and adolescents (1,3,(7)(8)(9) , despite the high processed food consumption among this population, which leads to high Na intake. We also observed a lack of studies in the literature about Na levels in Brazilian processed foods (21)(22)(23) , especially those targeted at children and adolescents (24,25) .…”
mentioning
confidence: 99%
“…Furthermore, a study that examined the content of pre-packaged children's food in Canada found that 62 % of products that were deemed to be of poor nutritional quality had a front-of-package nutritional claim (4) . As observed in the current study, that study also showed that front-ofpackage nutrition claims would highlight a single area of good nutrition such as 'source of calcium' and not mention that the same product was also high in sugar (4) . By highlighting a single positive nutrition claim, manufacturers have developed a powerful marketing strategy that aims to alter parental consumer behaviour by providing limited information about how their products fit into a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examining the nutritional content of baby/toddler foods available in the Canadian marketplace found that some products targeted at babies and toddlers actually contained more sugar and salt per serving than similar products targeted for adult consumption (3) . Another Canadian study found that 89 % of packaged products targeted at children were of poor nutritional quality (4) . This is even more surprising given that the study had excluded 'junk' foods such as candy, soft drinks, potato chips and cakes (4) .…”
mentioning
confidence: 99%
See 1 more Smart Citation